Karyotype and chromosome banding of endangered crucian carp, Carassius carassius (Linnaeus, 1758) (Teleostei, Cyprinidae) - Knytl, Martin; Kalous, Lukáš; Ráb, Petr (Comparative cytogenetics, 2013)
The karyotype and other chromosomal characteristics the crucian carp (Carassius carassius (Linnaeus, 1758)) were revealed by means of conventional banding protocols (C, CMA3, AgNOR). The diploid chromosome number (2n) in this species was 100. Its karyotype was composed of 10 pairs of metacentric, 18 pairs of submetacentric and 22 pairs of subtelo- to acrocentric chromosomes without any microchromosomes. C-banding identified blocks of telomeric heterochromatin on seven chromosome pairs. The NORs were situated on the p arms of the 14(th) pair of submetacentric chromosomes and on the p arms of the 32(nd) pair of subtelo-acrocentric chromosomes; AgNOR-positive signals corresponded to the CMA3-positive signals. These chromosome characteristics may suggest a paleo-allotetraploid origin of Carassius carassius genome.